Burnout in medical education: interventions from a co-creation process - Anke Boone; Lutgart Braeckman; Nele Michels; Kris Van den Broeck; Hanne Kindermans; Ann Roex; Marie-Claire Lambrechts; Sofie Vandenbroeck; Annabel Bijnens; Sofie Van den Acker; Sofie Boghe; Charlotte Vanneck; et al. (BMC Medical Education)
Abstract Introduction The high prevalence of burnout in medical education indicates an urgent need to develop and implement effective interventions at both the individual and organisational levels. Currently, there is a shortage of studies that include perspectives from multiple stakeholders, such as medical students, trainees and university staff. Our objective is to identify and discuss interventions from various stakeholders using a bottom-up approach to guide future implementation. Methods A co-creation methodology was adopted, including workshops and a Delphi session, engaging 96 participants. The study included 12 workshops with medical students and trainees in Flanders (Belgium): first-year bachelor students (n = 12), first-year master students (n = 13), first-year General Practice (GP) trainees (n = 14) and first-year specialist trainees (n = 39). Additionally, one Delphi session was held with 18 other relevant stakeholders, including university staff. All workshops were transcribed verbatim and thematically analysed using NVivo. Results Our results identified interventions to prevent and mitigate burnout among medical students and trainees. On the individual level, participants discussed personalized coaching, annual health assessments and training sessions. On the organisational level, a distinction was made between interventions intended for universities, and those for hospitals and GPs involved in medical training. Six interventions focused on preventing burnout in all contexts (i.e., onboarding programs); three were meant for universities only (i.e., pass-fail system), and six were tailored for hospitals and GPs (i.e., flexibility in scheduling). Conclusion Through an iterative multistakeholder co-creation process, this study identified interventions to prevent and mitigate burnout within medical education. These interventions span individual and organisational levels, targeting universities, hospitals and GPs. While organisational interventions are increasingly recognized as crucial to address burnout, individual-focused interventions remain predominant in current research. There is a pressing need to further investigate organisational interventions and their combination with individual-focused strategies.